Aleksandr Bogdanov’s Podbor and Proletkult: An Adaptive Systems Perspective - Dudley Peter (Cultural Science)
If one accepts (following Poustilnik 1995 and 1998) that Aleksandr Bogdanov’s intention in using the term podbor over otbor aimed at defining the process by which the ‘system in its environment’ comes into and continues in existence, one is also constrained to accept that such systems are active agents in the definition of self. Systems that create and maintain themselves in this way actively ‘assemble’ or construct themselves in reference to the nature of their relationship with their environments, rather than passively surviving in relation to environmental conditions. By extending this interpretation (of the choice of podbor over otbor) to the proletariat, as an individually and collectively adaptive system, it becomes possible to visualize the Proletkult as a conscious project to create an environment where it (the proletariat) could construct and adapt itself as a politically active, relevant and dominant class, thereby placing creative and cultural workers in the forefront of radical social change.